2016
DOI: 10.3389/fpsyg.2016.01636
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Pain Perception by Unconscious Emotional Pictures

Abstract: Pain perception arises from a complex interaction between a nociceptive stimulus and different emotional and cognitive factors, which appear to be mediated by both automatic and controlled systems. Previous evidence has shown that whereas conscious processing of unpleasant stimuli enhances pain perception, emotional influences on pain under unaware conditions are much less known. The aim of the present study was to investigate the modulation of pain perception by unconscious emotional pictures through an emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…I know the causes of disease.). It is widely known that cognitive distancing from pain increases the threshold of pain perception (Peláez, Martínez-Iñigo, Barjola, Cardoso, & Mercado, 2016). It was explicit that the beliefs in the theory of karma, rebirth, and incessant presence of divine powers were the major attributes of spiritual beliefs of the cancer survivors.…”
Section: Resultsmentioning
confidence: 99%
“…I know the causes of disease.). It is widely known that cognitive distancing from pain increases the threshold of pain perception (Peláez, Martínez-Iñigo, Barjola, Cardoso, & Mercado, 2016). It was explicit that the beliefs in the theory of karma, rebirth, and incessant presence of divine powers were the major attributes of spiritual beliefs of the cancer survivors.…”
Section: Resultsmentioning
confidence: 99%
“…A few papers have addressed this concept in terms of how unconscious processing may either enhance or inhibit (see (Pelaez et al, 2016) pain. As such, unconscious emotional processing of interactive positive or negative events, feelings, sights, may produce changes that enhance the behavioral manifestation of pain.…”
Section: When Pain Pops Out To Conscious Awareness – Insights Frommentioning
confidence: 99%
“…Examples include: (1) Experimental manipulation of subconsciousness can affect nociceptive processing (Lewis et al, 2015); (2) unconscious manipulation of the placebo or nocebo responses (Jensen et al, 2012a); (3) decreased pain perception modulated by unconscious emotional pictures (Pelaez et al, 2016); and (4) classical conditioning of pain without awareness of conditioning cues (Jensen et al, 2015). Unconscious perception – processing of sensory information that we are not aware of – has been evaluated in other systems including visual (Brogaard, 2011; Kiefer et al, 2011) and motor (Morsella and Poehlman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, it has been shown that images with negative valence affects visual-search performance (e.g., [ 37 ]). Similarly, there is evidence that images with different affective content (e.g., positive versus negative valence images) affect perceived pain intensity of different types of noxious stimulation (e.g., [ 2 3 , 38 39 ]; for a review see [ 13 ]). However, the effect of affective content on perceived pain intensity is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of affective content on perceived pain intensity is mixed. For example, Peláez et al [ 38 ] showed that subliminally presented negative emotional images decreased perceived pain intensity, whereas Kenntner-Mabiala et al [ 39 ] showed that viewing (supraliminal) negative emotional images increased perceived pain intensity. Second, attentional-bias models also incorporate the threat value of the noxious stimulation which—like affective content—can bias observers’ attention to pain signals rather than recruit attentional resources per se .…”
Section: Introductionmentioning
confidence: 99%